Aboveground biomass compartments of Pinus oaxacana stands under silvicultural regimes - Chávez-Pascual, Edwin Yoshimar; Rodríguez-Ortiz, Gerardo; Enríquez-del Valle, José Raymundo; Velasco-Velasco, Vicente Arturo; Gómez-Cárdenas, Martín (Instituto de Ecología, A.C., 2017)
Quantifying forest biomass of the forest is important in order to evaluate productivity and silvicultural regime effect. The objective of this study was to generate allometric models to estimate aboveground biomass of Pinus oaxacana and mixture of associated species as a response to silvicultural regimes. In Ixtlán, Oaxaca, Mexico, during 2014, 12 experimental units of 400 m2 were established in stands under different silvicultural regimes: 1) without treatment (conservation), 2) seed trees with 10-year regeneration, 3) seed trees with 15-year regeneration, 4) clearcutting with 7-year regeneration. With data obtained through destructive sampling (n = 69 individuals), allometric biomass models from the partial and total compartments of P. oaxacana, shrubby, in the forest floor and undergrowth were adjusted. In experiment under completely randomized design data were solved by analysis of variance, means test (Duncan, 0.05), cluster analysis and regression models. Allometric models that estimate between 88% and 98% of the aboveground biomass of Pinus oaxacana trees and shrubs and bush associated species use variables with easy measurement. The silvicultural regimes applied affected (p ≤ 0.05) aboveground biomass accumulated in specific and whole compartments of P. oaxacana, also the biomass in the forest floor, undergrowth and total aboveground. Likewise, stands under seed trees management (101.3 t ha-1) have the same aboveground total biomass than the conservation forest (125.74 t ha-1).